Association of Risk Perception and Information Provided on the Labels of Over-the-Counter Drugs: Role of Race, Education, Age and Income (Epidemiology, Biostatistics, and Public Health, 2022)
Background: The use of over-the-counter (OTC) drugs has increased tremendously, however, information on risk perception regarding the use of OTC drugs and their potential toxicity is scarce. Hence, the purpose of this study was to investigate the perception of OTC drug safety and efficacy based on reading product packaging and the effect of race, education, age and income. Methods: We used the HINTS 2012 data set with total sample size of 2,554. Results: OTC drug users having some high school education had a lower chance of frequently reading information included in the product labeling with the OTC medication. OTC drug users less than 50 years of age were always likely to read drug information on the OTC drug labeling. Also, Non-Hispanic blacks were more likely to read OTC drug labeling than Non-Hispanic whites.  OTC drug users less than 50 years of age consider OTC drugs safer than prescription drugs.  Conversely, OTC drug users with a high school, some college or bachelor’s degree consider OTC drugs less safe than prescription drugs.  Non-Hispanic blacks, non-Hispanic whites, and subjects of lower income were less likely to consider OTC drugs safer than prescription drugs.  OTC drug users with a high school education and some college perceive OTC drugs to be less effective than prescription drugs.Conclusion: To conclude, age, education, race, and income affect risk perception on OTC drugs.  Consumer information programs need to be designed so that meaningful results can be incorporated into public policy. Providing information on the labeling of OTC drugs and likelihood of patients reading this information require further study.